RANDOM BANACH-VALUED DIRICHLET SERIES WITH A INCREASING DETERMINISTIC SEQUENCE OF POSITIVE EXPONENTS - Skaskiv, O. B.; Kuryliak, M. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2022)
The article deals with random Dirichlet series of some form with monotone, increasing positive sequence of exponents and its coefficients are sequence of random variables on some probability space such that each mapping with the random variables is such that its norm is a measurable function with respect to pairs of sigma-algebras A and B(R), where B is complex-valued Banach space. The main statements of the paper are Theorems 1 and 2 and concern the estimates of the abscissas of convergence of the above series.